Hepatic mircocirculation and its role in development of pathological changes of the liver in experimental acute pancreatitis. - Zinenko, D. Yu.; Tverdokhlib, I. V. (Морфологія / Morphologia / Morfologìâ, 2019)
Background. The development of acute pancreatitis is not limited to isolated damage to the pancreas. After creating models of acute pancreatitis using various substances that enhance the secretion of the gland, have a toxic or local activating effect, the researchers showed their dose-dependent effect. The question of the reaction of the hepatic microcirculation system during the development of acute pancreatitis, as well as their pathogenetic significance in the development of pathomorphological changes in the liver in most aspects remains open. Objective. The purpose of the current study was to define the role of the hepatic mircocirculation in development of pathomorphological changes of the liver after the damage of pancreas in different rat models of experimental acute pancreatitis. Methods. The variants of 2 models were used: 1) model with intraperitoneal injection of L-arginin in dosage 3 g/kg; 4 g/kg and 5 g/kg; 2) model with injection 50 mkl 1%, 2,5% and 5% solutions of sodium taurocholat into pancreatic duct. The hystologic research of pancreas and liver were carried out in 1, 4, 8, 12, 24, 48 and 72 hours after initiation of inflammation. Results and conclusion. The visible reaction of hepatic mircocirculation in the experimental models of acute pancreatitis was depended on character of pathomorphological changes in pancreas. This reaction demonstrated the phase character including: 1) activation of hepatic circulation, first of all in portal component, against a background of pancreatic enzyme toxemia; 2) development of inflammatory, dystrophic, destructive and necrotic changes in hepatic parenchyme together with mircocirculation disorders against a background of pancreatic necrotic toxemia; 3) recovery and adaptation or decompensation processes in mircocirculation system of liver and hepatic parenchyme depending on the degree of pancreatogenic toxemia|.